2012
DOI: 10.1021/jf2046575
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Storage Effect on Berry Polyphenols: Challenges and Implications for Bioactive Properties

Abstract: Anthocyanins and tannins in blueberries, blackberries and black raspberries are susceptible to degradation during processing, with juices showing the greatest losses due to physical removal of skins and seeds. Anthocyanins and procyanidins are also degraded in processed products stored at ambient temperature with losses accompanied by increased polymeric pigments (PPs). Using chokeberry as a model, formation of PPs occurred in both pasteurized and aged juices and pasteurized juice contained a greater proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 100 publications
4
83
3
Order By: Relevance
“…Other than pyranoanthocyanins, polymeric pigments are a potential source of long-term color stability [21]. Polymeric pigments are the condensation product of anthocyanins and flavanols [22] and most often detected by MALDI-TOF-MS [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Other than pyranoanthocyanins, polymeric pigments are a potential source of long-term color stability [21]. Polymeric pigments are the condensation product of anthocyanins and flavanols [22] and most often detected by MALDI-TOF-MS [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Chrzczanowicz et al (2008) have shown that the consumption of 1 l of apple juice increased the blood serum antioxidant capacity of patients in just an hour, but over the next 4 h the value decreased to the baseline. Better results can be achieved by the consumption of berries rich in polyphenols (Howard et al 2012) and their products, especially juices (Piljac-Zegarac et al 2009). Chokeberry juice, for example, has a high content of bioactive compounds and high antioxidant capacity (Kapci et al 2013).…”
mentioning
confidence: 99%
“…The reduction of the antioxidant activity may be due to degradation of water soluble phenolic compounds such as anthocyanins and vitamin C [6,17]. The increase of the antioxidant activity was not at all surprising, as also reported by other studies [18][19][20] and can be explained by compounds generated during Maillard reaction and also by formation of procyanidins, low molecular polymers with antioxidant activity or by generation of other degradation products of anthocyanins or phenolic acids, compounds which also present antioxidant capacity [21,22].…”
Section: Resultsmentioning
confidence: 62%